PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN AURORA 3D PRESENTATION 2012 TERHADAP PEMAHAMAN KONSEP MATERI BANGUN RUANG SISWA KELAS VIII SMP NEGERI 10 KOTABUMI: PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN AURORA 3D PRESENTATION 2012 TERHADAP PEMAHAMAN KONSEP MATERI BANGUN RUANG SISWA KELAS VIII SMP NEGERI 10 KOTABUMI - Saridawati Saridawati; Muinah Muinah; Karsoni Berta Dinata (Universitas Muhammadiyah Kotabumi, 2022)
The development of interactive learning media using Aurora 3D Presentation 2012 for understanding the concept of building material for class VIII SMP Negeri 10 Kotabumi is motivated by the lack of use of computers as learning media for Aurora 3D Presentation 2012 especially mathematics. The use of learning media that is not optimal is one of the causes of students not understanding a good concept understanding, especially in the material of building space. This development was carried out with the aim of knowing the development process and the feasibility of learning media on interactive learning media using Aurora 3D Presentation 2012 for understanding the concept of building space. This development was carried out with the aim of knowing how to develop learning media based on Aurora 3D Presentation 2012. The development adopted by Sugiyono, research was limited to 7 stages of development, namely 1) potential and problems, 2) data collection, 3) product design, 4) design validation. , 5) design revision, 6) trial 7) Product revision due to limited time and cost. The type of data in this study used quantitative data and qualitative data. The results of this study are: (1) The products produced in this study include the product manufacturing stage, then validation and product revision are carried out; (2) The results of the validation test assessment by material experts are 90% with the